2017
DOI: 10.1080/17450128.2017.1282069
|View full text |Cite
|
Sign up to set email alerts
|

Pilot and feasibility study of a parenting intervention delivered by parent peers

Abstract: Preventive parenting interventions delivered by parent peer specialists may be a viable alternative to professional-led interventions and offer an advantage of increasing access in medically underserved areas. The objective of this pilot study was to assess the feasibility and preliminary outcomes of a 10-session, peer specialist-delivered preventive parenting intervention (Smart and Secure Children) for child disruptive behavior. The intervention was evaluated among a small sample of parents (N = 15) of presc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Similarly, results of various feasibility studies for caregivers of individuals with special needs have also demonstrated acceptability and satisfaction with the interventions. [41,49] Eighty two (82%) participants (dyads) practiced intervention exercises for > 1 month. Working hours of the husbands, varied household tasks of the wives, and distant living of relatives were among the few reasons for inconsistent practicing schedules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, results of various feasibility studies for caregivers of individuals with special needs have also demonstrated acceptability and satisfaction with the interventions. [41,49] Eighty two (82%) participants (dyads) practiced intervention exercises for > 1 month. Working hours of the husbands, varied household tasks of the wives, and distant living of relatives were among the few reasons for inconsistent practicing schedules.…”
Section: Discussionmentioning
confidence: 99%
“…Speci cally, 100 dyads consisting of a caregiver and a family volunteer, a total of 200 participants (100 caregivers and 100 family volunteers) were selected from the rehabilitation facility involved in the study. [41,42] Participants, who were stressed during the study or who needed medical help after completion of the study were referred to local mental health services, where they were attended to on a priority basis. Since no funding was available, no monetary compensation was given to the participants, however, refreshments were provided during the sessions.…”
Section: Methodsmentioning
confidence: 99%
“…Several caregiver support and skills training interventions to reduce stress associated with their child's care related to disruptive behaviors have been developed (Acri & Hoagwood, 2015;Barlow, Smailagic, Huband, Roloff, & Bennett, 2014;Gerkensmeyer et al, 2013;McKay et al, 2011;Williford & Shelton, 2008;Wittkowski, Dowling, & Smith, 2016). These interventions have demonstrated benefit in the areas of caregiver psychosocial functioning including depression, anxiety, stress (Barlow et al, 2014;Kuravackel et al, 2017;Da Paz & Wallander, 2017); caregiver competence and confidence (Barlow et al, 2014;Kuravackel et al, 2017); caregiver knowledge and management of their child's behavior problems (Butler & Titus, 2017;Kuravackel et al, 2017); and caregiver efficacy in navigating and accessing mental health and social services for their child (Jamison et al, 2017;Rodriguez et al, 2010). For example, Kutash, Duchnowski, Green, and Ferron (2011) found positive benefits in a parent-to-parent support group in caregiver perceived efficacy in obtaining needed mental health services for their child in special education.…”
Section: Caregiving For Adolescents With Odd/cd In Community Carementioning
confidence: 99%
“…Long-term treatment benefits have been demonstrated via within-group, waitlist control, and randomized control trials (RCTs). Other methods for determining the impact of parent-to-parent interventions entail the use of mediation analyses [27] and exploring the relationship between caregiver strain and treatment participation [25]. Assessing intervention effectiveness within the context of attrition and parent acceptability offers a unique insight for identifying the most helpful treatments that are available for whom, and under what conditions.…”
Section: Introductionmentioning
confidence: 99%